Hidden genetic diversity in snakeskin gourami, Trichopodus pectoralis (Perciformes, Osphronemidae), inferred from the mitochondrial DNA CO1 gene. Issue 2 (3rd July 2019) - Tan, Min Pau; Amornsakun, Thumronk; Siti Azizah, Mohd Nor; Habib, Ahasan; Sung, Yeong Yik; Danish-Daniel, Muhd
Abstract: Eighty-four specimens collected from 13 populations from Malaysia, Thailand, and Vietnam were analysed, revealing 21 putative haplotypes with overall estimated haplotype and nucleotide diversities of 0.79 and 0.0079, respectively. High levels of diversity and an absence of founder effects were observed among populations in peninsular Malaysia. In contrast, populations from Sarawak exhibited low genetic diversity, which is a typical sign of colonies introduced from a single source. Historical translocation of Trichopodus pectoralis from Thailand to Malaysia, as well as to the Philippines, Indonesia, and Myanmar was apparent. Historical introduction of T. pectoralis from Vietnam was also detected in peninsular Malaysia.